Writing history from parish records - Laeda, Ramon Danilo R. (2006)
In every Roman Catholic Parish, even those dating back to the Spanish colonial period, there is an archive where the Canonical Books are kept. The Canonical Books are the records of baptisms, marriages, confirmations, deaths, circulars, and accounts. The Book of Marriages is an important source of information for intermarriages among kin in one town in Ilocos Norte. The celebration of mass funerals from deaths caused by epidemics is information we can get from the Book of Deaths, while the Book of Confirmations gives us some clues as to the length of the interregnum from one ordained bishop to the other and the frequency of episcopal visitation of the parishes. The Libro de Recibo y Gastos tells us the income and expenses of a certain parish. The Libro de Ordenes Episcopales gives us a glimpse into the pastoral life of the Diocese through the directives of the bishops addressing pastoral concerns. This Canonical Books can go beyond their ordinary usage of determining baptisms, deaths, marriages, etc., and tell us what happened in the past. They could transform the historical to the historic, the dry bones of facts to an active record which may be useful to us at present and in the future.